The Readiness of EFL Teachers on Implemented of IKM of 2022 National Curriculum in Senior High School - Saputri, Kurnia; Hidajati, Enny; Budiyanto, Darmawan (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
These rapid changes did not give opportunities to EFL teachers to optimize their knowledge, mindset, commitment, and competences they had such as pedagogic, personal, social, and professional. When the majority of EFL teachers had not mastered yet how to implement the current curriculum at Senior High School’s (SHS’s) in South Sumatera, Palembang City, the new curriculum came. Thus, the implementation of the IKM at SHS’s in South Sumatera Palembang City varied. Some schools implemented the IKM only to class X, and Kl3 class XI and XII, and to class X, XI and XII. This situation indicated that there was a variation of readiness of EFL teachers in implementing the IKM. The result of the research showed that EFL teachers who became the participants of this research had not shown their readiness yet to implement the IKM following the national education standard. In other words, they remained in the contemplation stage (getting ready) in which EFL teachers in South Sumatera intend to change. They are still trying to implement the IKM properly in line with the national education standard. Thus, the result of this research can be used as a reference to improve EFL teachers’ competencies that affects the students’ competencies improvement.